2010
DOI: 10.1103/physrevb.82.153403
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry in Cu nanowires: N andN2enhancing the atomic chain formation

Abstract: We show using ab initio total-energy calculations based on density-functional theory how H, B, C, N, O, S, and N 2 impurities incorporated to thin copper nanowires could affect their mechanical properties and electronic structure. An interesting mechanochemical effect arises from the insertion of N and N 2 in the linear atomic chain. These impurities form not only stable but also very strong p-d bonds, in such a way that they can extract atoms from a stable tip enhancing the atomic chain suggesting the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…While Cu-Cu bonds tend to be in the range of around 2.2 to 2.7Å, the large distances provided by the effect of the atomic impurities are 3.47/3.54Å for H, 3.91/3.90Å for B, 3.66/3.68Å for C, 3.62/3.62Å for N, 3.60/3.62Å for O, and the largest of all 4.32/4.33Å for S, respectively, for LDA/GGA XC calculations. 34 These results correlate well with the order of the covalent radii of these elements, and HRTEM images similar to the ones produced in the case of Au NWs could verify these values. Figure 7 displays the PDOS of the LAC doped with N 2 impurity where we observed also the mechanochemical effect attributed to the incorporation of nitrogen.…”
Section: Electronic Structuresupporting
confidence: 79%
See 3 more Smart Citations
“…While Cu-Cu bonds tend to be in the range of around 2.2 to 2.7Å, the large distances provided by the effect of the atomic impurities are 3.47/3.54Å for H, 3.91/3.90Å for B, 3.66/3.68Å for C, 3.62/3.62Å for N, 3.60/3.62Å for O, and the largest of all 4.32/4.33Å for S, respectively, for LDA/GGA XC calculations. 34 These results correlate well with the order of the covalent radii of these elements, and HRTEM images similar to the ones produced in the case of Au NWs could verify these values. Figure 7 displays the PDOS of the LAC doped with N 2 impurity where we observed also the mechanochemical effect attributed to the incorporation of nitrogen.…”
Section: Electronic Structuresupporting
confidence: 79%
“…This becomes clear when we observe two distinct situations for each p electron in peaks ii and iii; they are perpendicular orbitals. Figure 4 displays the PDOS for the Cu LAC with N. In this distinct case, we observe the mechanochemical effect which causes the reconstruction of tips, enhancing the atomic chain size, resulting in a longer LAC, 34 clearly evidencing the strong bond formed between copper and nitrogen in this low coordination situation. This case shows two s electrons in peak i and three p electrons respectively for peaks ii, iii, and iv.…”
Section: Electronic Structurementioning
confidence: 89%
See 2 more Smart Citations
“…The addition of the impurity remarkably modifies both the mechanical stability and electronic properties of the clean nanowires. In addition, the formation processes of the thin Cu nanowires in the presence of the impurities (H, B, C, N, O, S or N 2 ) have been simulated by Amorim et al [26] using ab initio total energy calculations. They have shown that the N and N 2 contaminated Cu nanowires exhibit very strong p-d bonds, in such a way Cu atoms can be extracted from a stable tip and join into the wire upon stretching.…”
Section: Introductionmentioning
confidence: 99%